2022
DOI: 10.1007/s00431-022-04564-y
|View full text |Cite
|
Sign up to set email alerts
|

Sensory processing and adaptive behavior in Phelan-McDermid syndrome: a cross-sectional study

Abstract: Phelan-McDermid syndrome (PMS) is a genetic disorder caused by a mutation or deletion of the SHANK3 gene (chromosome 22q13.3), characterized by different sensory processing anomalies. The objective of this study is to expand and provide a detailed definition of the sensory profile of patients with PMS. The secondary objective was to examine the relationship between sensory patterns and adaptive behavior. A cross-sectional study was carried out among 51 Spanish patients with a confirmed genetic diagnosis of PMS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 48 publications
(86 reference statements)
1
4
1
Order By: Relevance
“…On the other hand, the results of our study have identified that the tactile sensory reactivity skills of the sample of participants with SSP are the only ones that showed significant changes after one year of follow-up. Compared to our previous results [ 23 ], a significant qualitative change has been identified in the signs associated with tactile sensitivity, mostly signs of hyperreactive behavioral responses. In this case, the changes indicate a probable, rather than definite, difference in participants with PMS.…”
Section: Discussioncontrasting
confidence: 98%
See 2 more Smart Citations
“…On the other hand, the results of our study have identified that the tactile sensory reactivity skills of the sample of participants with SSP are the only ones that showed significant changes after one year of follow-up. Compared to our previous results [ 23 ], a significant qualitative change has been identified in the signs associated with tactile sensitivity, mostly signs of hyperreactive behavioral responses. In this case, the changes indicate a probable, rather than definite, difference in participants with PMS.…”
Section: Discussioncontrasting
confidence: 98%
“…For the follow-up of the participants in the first phase of the study [ 23 ], the Spanish Short Sensory Profile (SSP-S) [ 39 ] was administered after the first assessment was completed. This questionnaire was completed by the primary caregiver.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Self‐injurious behaviors in PMS include head‐banging, skin‐picking, and biting. Sensory reactivity symptoms are common and most frequently characterized by hyposensitivity across sensory domains (Droogmans et al, 2020; Serrada‐Tejeda et al, 2022; Tavassoli et al, 2021; Mieses et al, 2016). An increased pain threshold is prevalent in PMS and can be associated with reduced response to potentially dangerous injuries (De Rubeis et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Individuals with Phelan McDermid Syndrome have characteristic traits including neonatal hypotonia, typically severe developmental delays (particularly in speech/language development), associated ASD, and some minor dysmorphic traits of the face and extremities ( 75 , 76 ). A number of affected individuals develop other associated conditions including seizures ( 75 , 77 ), sensory processing differences ( 78 , 79 ), and significant gastrointestinal disorders ( 80 ). Of additional import, individuals with this syndrome often have a broad and unsteady gait, and at times a loss of purposeful hand movements, which suggest cerebellar dysfunction, further implicating cerebro-cerebellar networks ( 71 ).…”
Section: Phelan Mcdermid Syndrome 22q13 Deletion and Other ...mentioning
confidence: 99%